Global macroeconomic burden of epilepsy and the role for neurosurgery: a modelling study based upon the 2016 Global Burden of Disease data. (20th October 2019) - O'Donohoe, T. J.; Choudhury, A.; Callander, E.
Abstract : Background and purpose: Although the significant morbidity and mortality burden associated with epilepsy is well understood, associated economic consequences are yet to be estimated on a global scale. We sought to: (i) estimate the value of lost economic welfare attributable to epilepsy among countries included in the 2016 Global Burden of Disease study, (ii) evaluate differences in disease burden between countries of varied income classification and location, and (iii) understand the proportion of this burden that requires neurosurgical consultation and intervention. Methods: Publicly available morbidity and mortality data were incorporated into a 'full‐income' model to generate estimates of the cumulative value of lost economic welfare (VLW) related to epilepsy. Results from a survey of neurosurgeons were then used to estimate the VLW attributable to the proportion of disease requiring neurosurgical consultation and intervention. Results: A total of 195 countries and territories were included in this analysis. We estimate that the cumulative VLW related to epilepsy was $647.37 billion [2016 US dollars (USD), purchasing power parity (PPP)]. Economic welfare losses were equivalent to a mean of 1.45% (±1.00%) of gross domestic product. The value of economic losses attributable to the proportion of the burden necessitating neurosurgical consultation and intervention was $258.95 billion (2016 USD, PPP) and $155.37 billion (2016 USD, PPP) respectively. Conclusions: Our results indicate that the economic consequences of epilepsy‐related morbidity and mortality are substantial. When considered with evidence supporting the cost‐effectiveness of various interventions for improved epilepsy diagnosis and management, our findings suggest that the implementation of simple and affordable measures may avert significant economic loss.